2020
DOI: 10.1073/pnas.2009233117
|View full text |Cite
|
Sign up to set email alerts
|

Thirst recruits phasic dopamine signaling through subfornical organ neurons

Abstract: Thirst is a highly potent drive that motivates organisms to seek out and consume balance-restoring stimuli. The detection of dehydration is well understood and involves signals of peripheral origin and the sampling of internal milieu by first order homeostatic neurons within the lamina terminalis—particularly glutamatergic neurons of the subfornical organ expressing CaMKIIa (SFOCaMKIIa). However, it remains unknown whether mesolimbic dopamine pathways that are critical for motivation and reinforcement integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 81 publications
2
25
0
Order By: Relevance
“…This raises the question of where in the brain is computed. The recent explosion of progress in unraveling the neurobiology of thirst ( 13 29 ) provides an unprecedented opportunity to link behavioral motivation to known neural mechanisms within an economic theory framework.…”
Section: Resultsmentioning
confidence: 99%
“…This raises the question of where in the brain is computed. The recent explosion of progress in unraveling the neurobiology of thirst ( 13 29 ) provides an unprecedented opportunity to link behavioral motivation to known neural mechanisms within an economic theory framework.…”
Section: Resultsmentioning
confidence: 99%
“…The recent explosion of progress in unravelling the neurobiology of thirst( 1428 ) provides an unprecedented opportunity to link behavioral motivation to known neural mechanisms within an economic theory framework. We have proposed that marginal utility MU could be re-interpreted dynamically, and showed that this can further explain the timing of behavioral choices (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine circuits have long been implicated in response vigor and willingness to work (47)(48)(49), as well as in representation of marginal utility (50). The SFO GLUT neurons modulate phasic responses in dopamine circuits during drinking (28), so dopamine circuits that encode in this task could inherit this information from SFO. Signals in insular and cingulate cortex related to predicted water need or hedonic water value (24)(25)(26)(27) may also be downstream of computation of in SFO.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal control of thirst and drinking behaviors are primarily mediated by circulating angiotensin II [52], which is upregulated during heat stress [53]. Angiotensin II regulates thirst at the subfornical organ (SFO) [54] and it was hypothesized that thirst signaling occurs through SFO dopaminergic efferents, some of which terminate in the POA [55]. Simplified representation of the mammalian thermoregulatory system.…”
Section: A Brief Mention: the Mammalian Thermosensory Pathwaymentioning
confidence: 99%